Molecular data allow to elucidate the taxonomic placement of some Umbelliferae from Middle Asia and Afghanistan (Pinacantha, Ladyginia, Peucedanum mogoltavicum) - Degtjareva, Galina V.; Pimenov, Michael G.; Samigullin, Tahir H. (Phytotaxa, 2018)
The systematic position of three Apiaceae-Apioideae taxa, Pinacantha porandica, Ladyginia bucharica and Peucedanum mogoltavicum, from Middle Asia and Afghanistan, is clarified based on nrITS DNA sequence data. In the molecular phylogenetic tree, the monotypic Pinacantha is placed in unresolved position within the Ferulinae. Although there is no morphological information on essential characters, we propose a new position of Pinacantha porandica within the genus Ferula. As a result a new combination Ferula porandica is proposed, with a new section Pinacantha to accommodate it. The attribution of Peucedanum mogoltavicum to Ferula has been confirmed, its correct name being Ferula lithophila. The genus Ladyginia should not be included in Ferula, its closest relatives being Mozaffariania and Glaucosciadium from the Glaucosciadium Clade.